IDENTIFICATION OF STUDENT ERRORS IN SOLVING DERIVATIVE PROBLEMS IN SMA NEGERI 3 PALANGKA RAYA - Janu Pinardi; Walter Punding; Suparman; Ardo Subagjo (JURNAL PENDIDIKAN, 2021)
This study aims to find out: (1) students' mistakes in solving problems derived from algebraic functions, and (2) the causes of studenterrors. This research is qualitative descriptive research, conducted in October until November 2020. The subjects in this study were 37 students of grade XI MIPA 3 SMA Negeri 3 Palangka Raya. Next, 3 students are selected for the interview, to find out why the student made a mistake. The instrument in this study consists of 5 test questions in the form of descriptions used to determine the type of mistakes made by students. Based on the results of the study, the types of mistakes made by students solve the problem of AlgebraIc Function Derivatives are: errors in facts, concepts, operations and principles Factors that cause students to make mistakes in solving problems derived from algebraic functions based on aspects of errors in understanding facts, concepts, operations and principles that contain students' knowledge of materials that have been learned from simple to difficult then students' memories of the concept of limits, root concepts and concepts of inverse , lack of ability to understand students to the material that has been studied such as understanding the concept of limit, root concept and concept of inverse. lack of ability to decipher material or apply material that has been studied in new situations and concerns the use of rules or principles such as applying the concept of limit, root concept, inverse concept and operating numbers.